2016
DOI: 10.4172/2155-9600.1000495
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prevalence of Anemia and Nutritional Status among Japanese Elderly Participants in the National Health and Nutritional Survey Japan, 2003-2009

Abstract: Objectives: This study aimed 1) to examine the trends in the prevalence of anemia of the Japanese elderly population and 2) to evaluate the association between hemoglobin concentrations and diet and lifestyle factors, by using data from a population-based, nationwide cross-sectional survey in Japan, from [2003][2004][2005][2006][2007][2008][2009]. Design:A cross-sectional nationally representative survey. Setting: Japan.Participants: A nationally representative sample of 10,606 community dwelling men (n=4656) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…According to a review of nutritional status survey measured by MNA-SF, the prevalence of the risk of malnutrition (score ≤11 points) was 8-76% among elderly in the community (18). The Japanese Centenarian Nutrition Survey showed that the proportion of malnutrition risk was 34.7% (10), while the proportion of malnutrition risk in our sample reached 87.6%, which may be related to the regional dietary differences (19,20). The risk of having such a high proportion of malnutrition among centenarians should be taken into account, given that a number of previous studies have shown that malnutrition in the elderly is associated with greater risks of acquiring consciousness disorders (21), depression (9), lower quality of life (22), and a higher 5-year mortality rate (23).…”
Section: Discussioncontrasting
confidence: 50%
“…According to a review of nutritional status survey measured by MNA-SF, the prevalence of the risk of malnutrition (score ≤11 points) was 8-76% among elderly in the community (18). The Japanese Centenarian Nutrition Survey showed that the proportion of malnutrition risk was 34.7% (10), while the proportion of malnutrition risk in our sample reached 87.6%, which may be related to the regional dietary differences (19,20). The risk of having such a high proportion of malnutrition among centenarians should be taken into account, given that a number of previous studies have shown that malnutrition in the elderly is associated with greater risks of acquiring consciousness disorders (21), depression (9), lower quality of life (22), and a higher 5-year mortality rate (23).…”
Section: Discussioncontrasting
confidence: 50%
“…Imai et al in their studies examined the prevalence of anemiaamong Japanese elderly population and evaluated the association between hemoglobin concentrations and diet factors. Their studies showed improved nutritional status of the Japanese elderly adults[4].Kawano et al studied the effect of Vitamin D supplementation on nephrolithiasis in rats [5]. In the research article Sofi et al studied the protective effect of buckwheat products on the development of cardiovascular disease by reducing oxidative stress [6].…”
mentioning
confidence: 99%